2009
DOI: 10.1534/genetics.109.102756
|View full text |Cite
|
Sign up to set email alerts
|

Association Studies Identify Natural Variation at PHYC Linked to Flowering Time and Morphological Variation in Pearl Millet

Abstract: The identification of genes selected during and after plant domestication is an important research topic to enhance knowledge on adaptative evolution. Adaptation to different climates was a key factor in the spread of domesticated crops. We conducted a study to identify genes responsible for these adaptations in pearl millet and developed an association framework to identify genetic variations associated with the phenotype in this species. A set of 90 inbred lines genotyped using microsatellite loci and AFLP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 46 publications
3
108
2
Order By: Relevance
“…We used this method to analyze our real data set. However, as highlighted by Saïdou et al (2009), this projection method does not necessarily lead to a valid kinship matrix (that is, a matrix with elements 40 and o1). Which is the best method when computing the r V 2 measure, either to use a valid kinship matrix or simply a valid variancecovariance matrix, remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…We used this method to analyze our real data set. However, as highlighted by Saïdou et al (2009), this projection method does not necessarily lead to a valid kinship matrix (that is, a matrix with elements 40 and o1). Which is the best method when computing the r V 2 measure, either to use a valid kinship matrix or simply a valid variancecovariance matrix, remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Natural variation in phytochrome responses has been detected in other species, including barley (Hordeum vulgare; Biyashev et al, 1997), oat (Avena sativa; Hou and Simpson, 1993), and Plantago lanceolata (Van Hinsberg, 1998), and single nucleotide polymorphisms at PHYB are candidates for causal linkage with clinal variation in bud set in Populus tremula (Ingvarsson et al, 2006). Several recent studies of candidate genes from multiple accessions have linked PHYC or PHYD variation to flowering time and/or morphological variation in Arabidopsis and millet Pennistum glaucum (Balasubramanian et al, 2006;Samis et al, 2008;Ehrenreich et al, 2009;Saïdou et al, 2009) and have identified geographic structuring at PHYA and PHYE in Cardamine nipponica (Ikeda et al, 2008(Ikeda et al, , 2009). The ultimate goal of most of these studies is to link traits to genes, and they provide insight into how light signaling works in natural environments (Maloof et al, 2000).…”
Section: Insights From Comparative Sequence Analysesmentioning
confidence: 99%
“…These data suggest that phyD and phyE contribute to the precision of responses to variable environments. Additionally, studies of variation in populations across a large spatial scale have linked clinal variation at PHYC with variation in flowering time (Balasubramanian et al, 2006;Saïdou et al, 2009), suggesting its role in photoperiod perception is relevant in natural environments.…”
Section: Additional Phytochromes: An Expanded Role For the Phytochrommentioning
confidence: 99%
“…Indeed, previous studies have reported that distinct photoreceptors are involved in local adaptation across several species (PHYC in A. thaliana, Balasubramanian et al 2006;Samis et al 2008; PHYB2 in Populus tremula, Ingvarsson et al 2006Ingvarsson et al , 2008 CRY1a in Glycine max, Zhang et al 2008; PHYE in C. nipponica, Ikeda et al 2009a; PHYC in Pennisetum glaucum, Saïdou et al 2009). Therefore, local adaptation implemented by photoreceptors cannot be attributed to a single type of photoreceptor across various species, but rather the photoreceptor that plays important roles in local adaptation would be dependent on the species, which might be determined by life cycle, distribution range, and/or demographic history.…”
Section: Evolution Of Photoreceptors In Cardamine Nipponicamentioning
confidence: 99%